Ibn Sahnun is a thinker And an educational guide (Journal of the College of Basic Education, 2022)
One of the scholars indicated that Arab scholars translated mathematics, medical and philosophical literature from the Greek, and that they were the first to introduce the Greek heritage to Europe.